Drug use and desicion making process for rational pharmacotherapy in elderly [Yaşlilarda i̇laç kullanimi ve rasyonel farmakoterapi̇ karari verme süreci̇] - (:unkn) unknown (My University, 2001)
The importance of drug use increased with the longer life expectancy in geriatric group. Elderly patients often have multiple chronic diseases, which lead them take many drugs, and pharmacokinetics and pharmacodynamic responses are altered with age. Since both factors increase adverse drug reaction incidence, greater attention to apply rational drug therapy principles is required in this population. Rational pharmacotherapy is a process defined by World Health Organization (WHO), which consists of defining patient's problem, specifying therapeutic objectives, choosing the drug(s) of proven efficacy and safety among different alternatives, and starting the treatment, by writing a good prescription and informing the patient about the disease and the treatment in a clear and understandable way. Then, the outcome of the treatment should be monitored appropriately. Organ functions decline; biochemical and pathological changes are seen, density, distribution, and sensitivity of receptors might alter; and post-receptor events and reflex responses change with age. All of these factors influence pharmacokinetic and pharmacodynamic properties of drugs. Therefore, the physician should prescribe optimum number of drugs of which (s)he knows the pharmacology well, preceded by an extensive questioning of the patient; start with a low dose, individualize the dose by close monitoring and pay attention to increase the patient's compliance to the treatment in geriatric population, knowing that drugs do have unwanted effects as well as benefical actions.
Keywords: Drug use; Geriatrics; Pharmacodynamics; Pharmacokinetics; Rational pharmacotherapy